Emerging Chiplet-Based Architectures for Heterogeneous Integration - Murali Krishna Reddy Mandalapu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the semiconductor industry's pivotal shift from traditional monolithic system-on-chip designs to chiplet-based architectures employing heterogeneous integration. As Moore's Law scaling encounters fundamental physical and economic barriers at advanced nodes, chiplet approaches offer a compelling alternative by disaggregating complex systems into smaller functional blocks manufactured separately and then integrated using advanced packaging technologies. This paradigm delivers substantial advantages in manufacturing yield, cost efficiency, development time, and performance optimization while enabling specialized acceleration for emerging workloads. The article explores how leading companies have implemented chiplet strategies, examines the critical role of advanced packaging technologies as enabling infrastructure, identifies key technical challenges requiring industry-wide solutions, and discusses how this architectural evolution is reshaping intellectual property models and business relationships throughout the semiconductor ecosystem. By exploring emerging research directions in three-dimensional integration, photonic interconnects, heterogeneous materials integration, and AI-optimized design tools, this work provides a comprehensive perspective on how chiplet-based architectures are fundamentally transforming semiconductor system design and manufacturing.
Keywords: Architecture; Chiplet; Heterogeneous; Integration; Semiconductor